Combination of medical needling and non-cultured autologous skin cell transplantation (ReNovaCell) for repigmentation of hypopigmented burn scars. Issue 7 (November 2016) - Busch, K.H.; Bender, R.; Walezko, N.; Aziz, H.; Altintas, M.A.; Aust, M.C.
Highlights: Combination of medical needling and skin cell transplantation to repigment burn scars was investigated. Objective evaluation of the melanin content of the skin was done pre- and postoperatively. Patient ratings and objective measures indicate improvement in scar pigmentation. Medical needling in combination with ReCell shows promise for repigmentation of burn scars. Abstract: Burn scars remain a serious physical and psychological problem for the affected people. Clinical studies as well as basic scientific research have shown that medical needling can significantly increase the quality of burn scars with comparatively low risk and stress for the patient with regards to skin elasticity, moisture, erythema and transepidermal water loss. However, medical needling has no influence on repigmentation of large hypopigmented scars. The goal of this study is to evaluate whether two established methods – needling (for improvement of scar quality) and non-cultured autologous skin cell suspension (for repigmentation) – can be successfully combined. Twenty subjects with mean age of 33 years (6–60 years) with scars from deep second and third degree burns have been treated. The average treated surface area was 94 cm 2 (15–250 cm 2 ) and was focused on prominent areas such as the face, neck, chest and arm. Percutaneous collagen induction or "medical needling" was performed using a roller covered with 3 mm long needles. The roller is vertically, horizontally and diagonally rolled over the scar, inducing microtrauma. Then, non-cultured autologous skin cell suspension (NCASCS) was produced and applied using the ReNovaCell Autologous Cell Harvesting Device (Avita Medical), according to the manufacturer's instructions. The patients were followed 12 months postoperatively. Pigmentation changes were measured objectively, as well as with patient and observer ratings. Patient satisfaction/preference was also obtained. Taken together, the pigmentation ratings and objective measures indicate individual improvement in 17 of the study participants. The melanin increases seen 12 months after NCASCS treatment are statistically significant. Medical needling in combination with NCASCS shows promise for repigmentation of burn cars.